Legitimacy of the Public Defender's Office in Civil Action: a view on the perspective of the hyposufficient people based on the judgment of the Federal Supreme Court (Research, Society and Development, 2022)
The aim of this work is to warn about attempts to limit the powers of the Public Defender's Office, especially with regard to the judgment of Extraordinary Appeal nº 733.433 of the State of Minas Gerais, in which Minister Dias Toffoli was the rapporteur, which was brought by the municipality of Belo Horizonte against the decision of the judgment handed down by the Seventh Civil Chamber of the Court of Justice of Minas Gerais, having as a claim at the time that the Public Defender's Office's legitimacy to file a public civil action be declared unconstitutional, on the grounds that there was no existence of a constitutional provision to guide the agency's performance in the active pole of public civil actions. Thus, after analyzing the aforementioned decision in conjunction with the new discussion through the Direct Action of Unconstitutionality No. of Public Defenders to request "from the public authority, or its agents, examinations, certificates, expertise, inspections, diligences, processes, documents, information, clarifications and measures necessary for the exercise of their attributions". history in Brazil between the authorities and society, especially when the subject is related to the realization of fundamental rights provided for in CF/88, hence it is clear that the disadvantaged are always the hyposufficient people, therefore, it is concluded that the constant attacks on the Public Defender's Office Public, makes it difficult for the needy to access justice.